Recent advanced strategies for bimetallenes toward electrocatalytic energy conversion reactions - Sanati, Soheila; Wang, Qiyou; Abazari, Reza; Liu, Min (Chemical communications (Cambridge, England), 2024)
Designing low-dimensional nanomaterials is vital to address the energy and environmental crisis by means of electrocatalytic conversion reactions. Bimetallenes, as an emerging class of 2D materials, present promise for electrocatalytic conversion reactions. By leveraging atomically thin layers, bimetallenes present unsaturated surface coordination, high specific surface area and high conductivity, which are all indispensable features for heterogeneous electrochemical reactions. However, the intrinsic activity and stability of bimetallenes needs to be improved further for bimetallene electrocatalysts, due to the higher demands of practical applications. Recently, many strategies have been developed to optimize the chemical or electronic structure to accommodate transfer of reactants, adsorption or desorption of intermediates, and dissociation of products. Considering that most such work focuses on adjusting the structure, this review offers in-depth insight into recent representative strategies for optimizing bimetallene electrocatalysts, mainly including alloying, strain effects, ligand effects, defects and heteroatom doping. Moreover, by summarizing the performance of bimetallenes optimized using various strategies, we provide a means to understand structure-property relationships. In addition, future prospects and challenges are discussed for further development of bimetallene electrocatalysts. Designing low-dimensional nanomaterials is vital to address the energy and environmental crisis by means of electrocatalytic conversion reactions.